Global scientific production on gasless laparoscopy: a bibliometric analysis - Pérez-Reátegui, Javier; Arge-Gamarra, Brad Jhefferson; Díaz-Ruiz, Renato; Hernández-Vásquez, Akram (Frontiers in Surgery, 2024)
Objectives. To characterize the bibliometric characteristics of the global scientific production of original research on gasless laparoscopy in the Web of Science Core Collection (WoSCC) platform.A bibliometric study of original articles published up to the year 2023 was carried out. Articles were included following the selection criteria in the Rayyan web application, indexed in the Scopus database. The bibliometric analysis was performed using the Bibliometrix program in the R programming language and VOSviewer. The bibliometric characteristics evaluated were articles, journals, citations, publications, ten most mentioned articles, journals with the highest number of publications, authors and institutional affiliations; and cooccurrence of terms. Results. A total of 223 publications were included, with the highest number of articles being published in the years 1999 and 2014. The publication with the most citations was found to be a randomized trial by Galizia G in 2001 with 132 citations. We identified 846 authors involved in the production of articles on gasless laparoscopy, with Nakamura H being the most productive author with 15 articles between the years 2007 and 2020, followed by Takeda A and Imoto S, all three affiliated with "Gifu Prefectural Tajimi Hospital". The country with the highest production was Japan with 64 publications, followed by China and Italy with 46 and 18 publications, respectively. In the top 10 journals with the highest number of publications, "Surgical Endoscopy -Ultrasound and Interventional Techniques" is in first place with 20 articles published on gasless laparoscopy; in addition, most of these are located in Q1 and Q2. Regarding the terms or keywords, it was found that the initial studies had terms related to the disadvantages of pneumoperitoneum and later focused on more specific topics of the application of gasless laparoscopy. Conclusions. Production on gasless laparoscopy has stagnated, with the topics of interest currently being its application in new, less invasive techniques. The most productive countries are found in the Asian and European continents, with little information collected in Latin America. This fact makes it necessary to increase the production of studies to promote this technique and its possible advantages.